Uncontrolled DCD: When Should We Stop Trying to Save the Patient and Focus on Saving the Organs? - Ortega-Deballon, Iván (The Hastings Center report, 2018)
Uncontrolled donation after circulatory death, which occurs when an individual has experienced unexpected cardiac arrest, usually not in a hospital, generates both excitement and concern. On the one hand, uDCD programs have the capacity to significantly increase organ donation rates, with good transplant outcomes—mainly for kidneys, but also for livers and lungs. On the other hand, uDCD raises a number of ethical challenges. In this essay, we focus on an issue that is central to all uDCD protocols: When should we cease resuscitation and shift to organ preservation? Do current uDCD protocols prematurely consider as potential donors patients who could still have some chances of meaningful survival? Can the best interest of patients be fostered once they are considered and treated as potential donors?